Implementasi Outcome Based Education (OBE) dalam pengembangan Kurikulum Pendidikan Islam Berbasis Surah Luqman Ayat 12-19: RELEVANTION OF OUTCOME-BASED EDUCATION (OBE) IN THE DEVELOPMENT OF AN ISLAMIC EDUCATION CURRICULUM BASED ON SURAH LUQMAN (12-19) - mustofiyah, anis marifatul; razzaq, abdur; imron, kristina; Takrip, Muhamad (Qolamuna : Jurnal Studi Islam, 2026)
This study highlights the application of Outcome Based Education (OBE) in the development of an Islamic Education curriculum based on the values of Surah Luqman verses 12–19. The study was conducted using a qualitative literature review method. Data analysis was carried out using data reduction from relevant studies. The findings of the study show that Outcome-Based Education focuses on clear, measurable learning outcomes that are relevant to the needs of society and the world of work. This concept was then combined with the values contained in Surah Luqman verses 12–19, namely the outcomes that Luqman expected from his descendants, namely to be monotheistic, uphold the Sharia, and have good character. Thus, Surah Luqman verses 12–19 became an important foundation in formulating the objectives of Islamic Education in line with the principles of modern Islamic-based education. Therefore, OBE design should not only focus on cognitive aspects but also integrate spiritual, moral, and social dimensions. With the support of Qur'anic values, an OBE-based curriculum is expected to produce graduates who are highly competent, possess Islamic character, and are ready to face the challenges of the global future. Keywords : Outcome Based Education, Islamic Education, Surah Luqman ayat 12-19